Ecosystem-specific controls of denitrifier gene abundance and community composition on potential nitrous oxide emissions in upland and paddy soils - Xianchu Su; Guiping Ye; Hang-Wei Hu; Mengmeng Feng; Luyuan Sun; Yuheng Cheng; Zi-Yang He; Jia Liu; Yongxin Lin (Soil Ecology Letters, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Gadolinium-based metal-organic framework with restriction of aggregation-caused quenching effect synergized high-activity pt-single-atom catalyst for multiplex self-enhanced electrochemiluminescence sensing detection of kanamycin - Ling Wu; Kaiwen Yang; Yumeng Qin; Wen Hao; Lin Cai; Mengmeng Guo; Guozhen Fang; Shuo Wang (Food Research International, 2026)

Amino Acid Metabolic Remodeling in Bivalves Under Environmental Stress: Roles, Mechanisms, and Implications for Bivalve Health—A Review - Yichen Lin; Wei Chen; Jixing Peng; Xinnan Zhao; Yan Di; Mengmeng Guo; Yanfang Zhao; Haiyan Wu; Guanchao Zheng; Qianqian Geng; Zhijun Tan (Fishes, 2026)
Climate change and increasing instability in coastal marine environments have intensified stressors such as elevated temperature, hypoxia, salinity variation, and pollutant exposure, posing major challenges to the survival, health, and culture performance of bivalves. As economically important aquaculture species and key components of coastal ecosystems, bivalves are highly sensitive to environmental fluctuations, making their metabolic responses highly relevant to both physiological adaptation and aquaculture sustainability. Increasing evidence indicates that metabolic remodeling is an important adaptive strategy supporting bivalve tolerance to environmental stress, with amino acid metabolic remodeling emerging as one of its most sensitive and functionally important components. This review summarizes the major response patterns, key pathways, and potential regulatory mechanisms of amino acid metabolism in bivalves under different stress conditions. Different environmental stressors induce distinct yet integrated shifts in amino acid metabolism, including enhanced catabolism, carbon–nitrogen redistribution, osmotic regulation, and antioxidant defense, thereby supporting energy homeostasis and physiological stress tolerance in bivalves. By highlighting amino acid metabolic remodeling as a central mechanism of bivalve adaptation to environmental stress, this review provides insights into adaptive responses, metabolite-based indicators for monitoring aquaculture environments and bivalve health, and management strategies for improving resilience in bivalve aquaculture.

Retraction notice to “A systematic review of antibiotics and antibiotic resistance genes (ARGs) in mariculture wastewater: Antibiotics removal by microalgal-bacterial symbiotic system (MBSS), ARGs characterization on the metagenomic” [Sci. Total Environ. 930 (2024) 172601] - Weijia Gong; Lin Guo; Chenxin Huang; Binghan Xie; Mengmeng Jiang; Yuzhou Zhao; Haotian Zhang; YuXuan Wu; Heng Liang (Science of The Total Environment, 2026)

The influence of microplastic polymer characteristics on estuarine phosphorus dynamics through microbial mediation: A field study in the Pearl river estuary - Wei Lin; Jiansheng Zhou; Jiajun Huang; Mengmeng Jiang; Minjie Wang; Yili Wang; Ruifen Jiang; Guanlan Wu; Zihao Wu; How Yong Ng (Environmental Research, 2026)

Early Cotton Fields Mapping Using a Deep Learning Model Integrating Effective Accumulated Temperature and Multi-Source Remote Sensing Data - Xiaoqin Wang; Jun Ye; Jieni Liu; Mengmeng Li; Mengjing Lin; Qunyong Wu (Advances in Space Research, 2026)

Directed synthesis, characterization and rheological properties of an ultrahigh molecular weight acetylated-gellan gum - Yue Ming; Zhuangzhuang Shi; Weilong Wang; Jue Li; Yiting Lin; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Ytterbium/zinc hierarchically modulated aggregation-induced emission active metal-organic framework for ratiometric-electrochemiluminescence and fluorescence dual-mode detection of nitrofurazone - Wen Hao; Lin Cai; Guangrao Chen; Mengmeng Guo; Jie Wu; Guozhen Fang; Shuo Wang (Chemical Engineering Journal, 2026)

Engineering compartmentalized utilization of glycerol with glucose for high-level chondroitin production in Corynebacterium glutamicum - Zhuangzhuang Shi; Yue Ming; Jue Li; Yiting Lin; Weilong Wang; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

The key predictive factors of arbuscular mycorrhizal fungi community spatial distribution in saline-alkaline meadow soils: Abiotic variables or hosts? - Lin Zhang; Yuqiang Wen; Mengmeng Zhang; Kun Li; Ruotong Wu; Ning Sun; Fuqiang Song; Tianle Xu (Rhizosphere, 2026)

Spatiotemporal linkage between carbon storage and heat mitigation effects from land use change in the hokkien golden triangle: an InVEST analysis - Jiawei Huang; Mengjing Lin; Xiaoqin Wang; Mengmeng Li; Mingsong Zhao (Environment, Development and Sustainability, 2026)

Investigation of intramolecular split G-quadruplex-hemin systems and development of DNAzyme-based probes - Lu Lin; Mengmeng Lv; Jiangtao Ren; Jin Wang; Erkang Wang (Analytica Chimica Acta, 2026)

Satellite-observed first large-scale Sargassum bloom in the northern South China Sea - Longxiao Zheng; Xinliang Pan; Lin Qi; A Runa; Yanfang Xiao; Keunyong Kim; Rongjie Liu; Mengmeng Cao; Yanwei Song; Joo-Hyung Ryu; Tingwei Cui (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Insight into the synergistic inhibition of oyster pentapeptide (Phe-Pro-Val-Gly-Arg) and peonidin-3-O-glucoside against DPP-IV and their interactions - Xiaojie Su; Mengmeng Zhang; Wenhong Cao; Longjian Zhou; Mingtang Tan; Guoping Zhu; Jialong Gao; Haisheng Lin; Zhongqin Chen (Food Research International, 2026)

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Maternal Genetic Diversity Analysis of Guanling Cattle by Mitochondrial Genome Sequencing - Longxin Xu; Xin Wang; Hua Wang; Junda Wu; Wenzhang Zhou; Mengmeng Ni; Kaikai Zhang; Yuanfeng Zhao; Ruiyi Lin (Biochemical Genetics, 2025)

Biofilm management via loach predation: An eco-friendly approach to enhance membrane performance in wastewater treatment - Weijia Gong; Xianwu Liu; Yuzhou Zhao; Mengmeng Jiang; Lin Guo; Le Tong; Jinyan Lu; Jiaxuan Yang; Heng Liang; Xiaobin Tang (Chemical Engineering Journal, 2025)

Flavonoid-mediated metabolic underpinning quality variation in red bud-sport pear mutants - Wenyuan Li; Menghua Lin; Wayne Jiang; Xiaoxing Wu; Mengmeng Wang; Ying Liang; Zhiyong Zhang (Food Chemistry, 2025)

Estimation of Strain-Softening Parameters of Marine Clay Using the Initial T-Bar Penetration Test - Qinglai Fan; Zhaoxia Lin; Mengmeng Sun; Yunrui Han; Ruiying Yin (Journal of Marine Science and Engineering, 2025)
T-bar penetrometers have been widely used to measure strength parameters of marine clay in laboratory and in situ tests. However, using the deep resistance factor derived from full-flow conditions to evaluate the undrained shear strength of shallow clay layers may lead to significant underestimation. Furthermore, the deep resistance factor is inherently influenced by the strain-softening behavior of clay rather than maintaining the constant value (typically 10.5) as conventionally assumed in practice. To address this issue, large-deformation finite element (LDFE) simulations incorporating an advanced exponential strain-softening constitutive model were performed to replicate the full T-bar penetration process—from shallow embedment to deeper depths below the mudline. A series of parametric studies were conducted to examine the influence of key parameters on the resistance factor and the associated failure mechanisms during penetration. Based on numerical results, empirical formulas were derived to predict critical penetration depths for both trapped cavity formation and full-flow mechanism initiation. For penetration depths shallower than the full-flow depth, an expression for the softening correction factor was developed to calibrate the shallow resistance factor. Finally, combined with global optimization algorithms, a computer-aided back-analysis procedure was established to estimate strain-softening parameters using resistance-penetration curves from initial penetration tests in marine clay. The reliability of the back-analysis procedure was validated through extensive comparisons with a series of numerical simulation results. This procedure can be applied to the interpretation of T-bar in situ test results in soft marine clay, enabling the evaluation of its strain-softening behavior.

Effect of protein oxidation on the structural characteristics and emulsification properties of rice bran protein fibril: Assessing the role of peroxyl radicals - Mengmeng Zhao; Xiaojuan Wu; Haitong Tan; Lizhong Lin; Wei Wu (Food Chemistry, 2025)

Improved ALT retrieval in the Yellow River source region using time-series InSAR and multilayer soil moisture modeling - Zhengjia Zhang; Qingguang Jin; Lin Liu; Mengmeng Wang; Xuefei Zhang (Journal of Hydrology, 2025)

Characterization and sources of childhood PAEs exposure from residential airborne dust in China cities - Chao Wang; Shuhan Gong; Yun Cao; Mengmeng Liu; Wenying Zhang; Xiaotong Zhang; Lin Fan; Li Li; Hang Du; Mats Tysklind; Xu Yang; Xianliang Wang (Journal of Environmental Sciences, 2025)

A molecularly imprinted near-infrared electrochemiluminescence sensor based on copper nanowires and signal dual-amplification strategy for the sensitive detection of enrofloxacin - Jie Wu; Ling Wu; Mengmeng Guo; Wen Hao; Lin Cai; Guozhen Fang; Shuo Wang (Food Chemistry, 2025)

A 3-Year Environmental Surveillance Reveals Multiple Enteroviruses Including Types A76, A89, A90 and C113 in Eastern China - Xiaojuan Lin; Mingyi Xu; Yonglin Han; Feng Ji; Suting Wang; Meng Chen; Mengmeng Wang; Aiqiang Xu; Zexin Tao (Food and Environmental Virology, 2025)

Evaluation on the antiviral activity of aloe emodin against Micropterus salmoides rhabdovirus in vitro and in vivo - Yao Wang; Mengmeng Wang; Zhiyang Lin; Guangshuo Wang; Yunlong Qin; Mingzhu Liu; Fei Ling; Haifeng Jiang; Tianqiang Liu; Gaoxue Wang (Aquaculture, 2025)

Extracting vectorized agricultural parcels from high-resolution satellite images using a Point-Line-Region interactive multitask model - Mengmeng Li; Chengwen Lu; Mengjing Lin; Xiaolong Xiu; Jiang Long; Xiaoqin Wang (Computers and Electronics in Agriculture, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

Long-term exposure to ambient air pollutants and risk of prostate cancer: A prospective cohort study - Yu Chen; Siru Yang; Jiahao Lin; Shaohua Gu; Lan Wu; Wenkai Huang; Jun Yang; Mengmeng Li (Environmental Research, 2025)

Green manuring increases network complexity and deterministic assembly of diazotrophic community in a subtropical paddy soil - Xianchu Su; Luyuan Sun; Yuntao Kang; Mengmeng Feng; Junkang Zhu; Anqi Wang; Zi-Yang He; Shengsheng Jin; Jia Liu; Ji-Zheng He; Yongxin Lin (Applied Soil Ecology, 2025)

Nitrogen-removed organic matters from cyanobacterial decomposition promote the release of nitrogen from lake sediment - Mengmeng Wang; Yixuan Zhan; Chenyu Wang; Xiaohua Song; Lin Gan; Hao Lu; Liuyan Yang (Environmental Science and Pollution Research, 2025)

A study on the impact of meteorological and emission factors on PM2.5 concentrations based on machine learning - Chenxu Zhao; Zejian Lin; Leifeng Yang; Mengmeng Jiang; Zhubing Qiu; Siyu Wang; Yu Gu; Wei Ye; Yusuo Pan; Yong Zhang; Tianxin Wang; Yong Jia; et al. (Journal of Environmental Management, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Metabolomic profiling reveals the anti-herbivore mechanism of rice (Oryza sativa) induced by silicon - Chengzhen Gu; Mengmeng Wang; Yangzheng Lin; Yujia Zhang; Afsar Khan; Yuanyuan Song; Rensen Zeng (Arthropod-Plant Interactions, 2025)

Electron-deficient wastewater treatment in membrane-aerated conductive biofilm reactor: Performance and mechanism - Weijia Gong; Han Zhang; Minghao Xue; Lin Guo; Mengmeng Jiang; Yuzhou Zhao; Heng Liang (Bioresource Technology, 2024)

Global associations between long-term exposure to PM2.5 constituents and health: A systematic review and meta-analysis of cohort studies - Sujuan Chen; Di Liu; Lin Huang; Cui Guo; Xiaoke Gao; Zhiwei Xu; Zhou Yang; Yu Chen; Mengmeng Li; Jun Yang (Journal of Hazardous Materials, 2024)

Nasopharyngeal carcinoma cell screening based on nuclear targeting Surface-Enhanced Raman Scattering (SERS) detection - Mengmeng Zheng; Yahui Ren; Lei Jing; Meidie Cheng; Juqiang Lin; Yun Yu (Analytica Chimica Acta, 2024)

RETRACTED: A systematic review of antibiotics and antibiotic resistance genes (ARGs) in mariculture wastewater: Antibiotics removal by microalgal-bacterial symbiotic system (MBSS), ARGs characterization on the metagenomic - Weijia Gong; Lin Guo; Chenxin Huang; Binghan Xie; Mengmeng Jiang; Yuzhou Zhao; Haotian Zhang; YuXuan Wu; Heng Liang (Science of The Total Environment, 2024)

Effects of rice bran rancidity on the interfacial adsorption properties of rice bran protein fibril aggregates and stability of high internal phase Pickering emulsions - Mengmeng Zhao; Fang Li; Helin Li; Qinlu Lin; Xiaoling Zhou; Xiaojuan Wu; Wei Wu (Food Chemistry, 2024)

Shelterbelt effects on soil redistribution on an arable slope by wind and water - Yanru Wen; Bao Liu; Litao Lin; Mengmeng Hu; Xue Wen; Ting-Yong Li; Jiandong Rong; Shuihong Yao (CATENA, 2024)

Expression characteristics and interference analysis of glucose-6-phosphate dehydrogenase reveal its importance in Pyropia yezoensis under salt stress - Li Huan; Mengmeng Shi; Guohong Lin; Baoyu Zhang; Xiujun Xie; Menglin Guo; Xi Qiang; Zhaojia Ge; Jianfeng Niu; Zhenbing Zheng; Xulei Wang; Guangce Wang (Algal Research, 2024)

Higher stochasticity in comammox Nitrospira community assembly in upland soils than the adjacent paddy soils at a regional scale - Mengmeng Feng; Yongxin Lin; Zi-Yang He; Hang-Wei Hu; Shengsheng Jin; Jia Liu; Song Wan; Yuheng Cheng; Ji-Zheng He (Science of The Total Environment, 2024)

Effect of phlorotannins modification on the physicochemical, structural and functional properties of soybean protein isolate and controlled hydrolysates: Covalent and non-covalent interactions - Lin Cheng; Ziteng Lian; Xiuying Liu; Shicheng Dai; Lanxin Li; Mengmeng Wang; Ka Li; Kunyu Ren; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

The joint effects of mixture exposure to multiple meteorological factors on step count: A panel study in China - Ziqiang Lin; Mengmeng Wang; Junrong Ma; Yingyin Liu; Wayne R. Lawrence; Shirui Chen; Wangjian Zhang; Jianxiong Hu; Guanhao He; Tao Liu; Ming Zhang; Wenjun Ma (Environmental Pollution, 2024)

Microparticle deposition induced asymmetric adhesive hydrogel for suture-less gastric trauma treatment - Lei Liang; Hongda Wang; Linfa Li; Ding Lin; Bingyan Guo; Mengmeng Yao; Zhijian Wei; Hong Zhang; Junjie Li (Chemical Engineering Journal, 2024)

CRISPR/Cas9-mediated knockout of Bsr-d1 enhances the blast resistance of rice in Northeast China - Ying Zhang; Xiu-Feng Lin; Li Li; Ri-Hua Piao; Songquan Wu; Anqi Song; Mengmeng Gao; Yong-Mei Jin (Plant Cell Reports, 2024)

Cardiac energy metabolism disorder mediated by energy substrate imbalance and mitochondrial damage upon tebuconazole exposure - Tingting Ku; Jindong Hu; Mengmeng Zhou; Yuanyuan Xie; Yutong Liu; Xin Tan; Lin Guo; Guangke Li; Nan Sang (Journal of Environmental Sciences, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Spatiotemporal distribution, source analysis and ecological risk assessment of polychlorinated biphenyls (PCBs) in the Bohai Bay, China - Shan Jiang; Mengmeng Wan; Kun Lin; Yanshan Chen; Rui Wang; Liju Tan; Jiangtao Wang (Marine Pollution Bulletin, 2024)

Isolation, identification of antioxidant peptides from earthworm proteins and analysis of the structure–activity relationship of the peptides based on quantum chemical calculations - Ping He; Yi Zhang; Yizhe Zhang; Lina Zhang; ZhengLi Lin; Chongzhen Sun; Hui Wu; Mengmeng Zhang (Food Chemistry, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Design and application of zirconium-based coordination polymers for selective capture of copper - Dekun Zhang; Likang Fu; Mengmeng Zhang; Shixing Wang; Chao Xiong; Guo Lin; Libo Zhang (Journal of Environmental Chemical Engineering, 2023)

Dual-channel MIRECL portable devices with impedance effect coupled smartphone and machine learning system for tyramine identification and quantification - Zhiwei Lu; Jun Qin; Chun Wu; Jiajian Yin; Mengmeng Sun; Gehong Su; Xianxing Wang; Yanying Wang; Jianshan Ye; Tao Liu; Hanbing Rao; Lin Feng (Food Chemistry, 2023)

Immunomodulatory effect of earthworm protein autolysates on Cyclophosphamide(CTX)-Induced immunosuppressed mice - Yizhe Zhang; Ping He; Leiman Pan; Zhengli Lin; Jinxi Yang; Hui Wu; Mengmeng Zhang (Food Bioscience, 2023)

Bavachin combined with epimedin B induce idiosyncratic liver injury under immunological stress conditions - Mengmeng Lin; Yingying Li; Bo Cao; Jing Xu; Yujun Zhang; Guohui Li; Xiaohe Xiao; Chunyu Li (Chemico-Biological Interactions, 2023)

GATraj: A graph- and attention-based multi-agent trajectory prediction model - Hao Cheng; Mengmeng Liu; Lin Chen; Hellward Broszio; Monika Sester; Michael Ying Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Efflux transport proteins of Tetrahymena thermophila play important roles in resistance to perfluorooctane sulfonate exposure - Mengmeng Wang; Bingyu Song; Tianyu Song; Kailun Sun; Jin He; Jiewei Deng; Ling Fang; Tiangang Luan; Li Lin (Journal of Hazardous Materials, 2023)

Isolation, identification, and structure-activity relationship of novel ACE inhibitory peptides from earthworm protein in vitro gastrointestinal digestion product - Zhengli Lin; Hui Wu; Mengmeng Zhang (Food Bioscience, 2023)

Effects of linking group on the desalination performance of three-dimensional covalent organic framework membranes - Mengjiao Guan; Qingzhi Liu; Huiting Zhang; Qing Li; Jianan Xu; Mengmeng Cai; Weike Lin; Weina Li; Dengfeng Yang (Desalination, 2023)

Impact of three phycospheric bacterial strains on the growth and fatty acid composition of Isochrysis galbana - Minnan Wu; Jiayi Cao; Yijun Xu; Simin Xu; Zhengbo Zhou; Mengmeng Shao; Ziyue Wang; Lin Zhang; Deshui Chen; Yuanyuan Wu; Jilin Xu; Xiaojun Yan (Algal Research, 2023)

Total sleep deprivation impairs visual selective attention and triggers a compensatory effect: evidence from event-related potentials - Tao Song; Lin Xu; Ziyi Peng; Letong Wang; Cimin Dai; Mengmeng Xu; Yongcong Shao; Yi Wang; Shijun Li (Cognitive Neurodynamics, 2023)

Levels, distribution, childhood exposure assessment, and influencing factors of polybrominated diphenyl ethers (PBDEs) in household dust from nine cities in China - Jing Qi; Xiaoli Wang; Lin Fan; Shuhan Gong; Xinqi Wang; Chong Wang; Li Li; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Impact of commercial cooking on urban PM2.5 and O3 with online data-assisted emission inventory - Yingzhi Yuan; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Yanghong Xie; Haixian Li; Jia Xing; Bin Zhao; Mengmeng Zhang; Zhiqiang You (Science of The Total Environment, 2023)

Projecting the excess mortality due to heatwave and its characteristics under climate change, population and adaptation scenarios - Jiangdong Liu; Hang Dong; Mengmeng Li; Ying Wu; Chunlin Zhang; Jinjian Chen; Zhou Yang; Guozhen Lin; De Li Liu; Jun Yang (International Journal of Hygiene and Environmental Health, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Screening, ACE-inhibitory mechanism and structure-activity relationship of a novel ACE-inhibitory peptide from Lepidium meyenii (Maca) protein hydrolysate - Zhengli Lin; Junwen Lai; Ping He; Leiman Pan; Yizhe Zhang; Mengmeng Zhang; Hui Wu (Food Bioscience, 2023)

Levels, distribution, sources and children health risk of PAHs in residential dust: A multi-city study in China - Xinqi Wang; Xiaoli Wang; Jing Qi; Shuhan Gong; Chong Wang; Li Li; Lin Fan; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Accessing people's attitudes towards garbage incineration power plants: Evidence from models correcting sample selection bias - Mengmeng Xu; Boqiang Lin (Environmental Impact Assessment Review, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Impact of miR-200b and miR-495 variants on the risk of large-artery atherosclerosis stroke - Shanmei Qin; Chong Shen; Wuzhuang Tang; Mengmeng Wang; Ying Lin; Zhaojun Wang; Yunzi Li; Zhizhong Zhang; Xinfeng Liu (Metabolic Brain Disease, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

The synergistic mechanism of β-lactam antibiotic removal between ammonia-oxidizing microorganisms and heterotrophs - Ning Guo; Mengmeng Liu; Zhuhui Yang; Daoji Wu; Feiyong Chen; Jinhe Wang; Zhaoliang Zhu; Lin Wang (Environmental Research, 2023)

Facile fabrication of a 2D/2D CoFe-LDH/g-C3N4 nanocomposite with enhanced photocatalytic tetracycline degradation - Mengxue Li; Mengmeng Chen; Stephanie Ling Jie Lee; Sijie Lin (Environmental Science and Pollution Research, 2023)

Enhanced visible light-driven photodegradation of tetracycline by salicylic acid-modified graphitic carbon nitride and toxicity assessment - Mengmeng Chen; Mengxue Li; Peng Li; Stephanie Ling Jie Lee; Juanjuan Tang; Qian Li; Sijie Lin (Environmental Science and Pollution Research, 2022)

Taxonomy and phylogeny of Pseudovorticella ciliates (Ciliophora, Peritrichia): Two new and one rare species from the coastal waters of China - Yong Zhang; Ying Yu; Zhishuai Qu; Mengmeng Jiang; Zhuo Shen; Jiqiu Li; Xiaofeng Lin (Frontiers in Marine Science, 2022)
Peritrich ciliates are a species-rich group of sessile unicellular eukaryotes, which can be found in various aquatic habitats from all over the world. It is well accepted that there are still many ciliates to be uncovered. During a survey on ciliate biodiversity in the coastal waters of China, three solitary peritrich species were identified as members of the genus Pseudovorticella Foissner & Schiffmann, 1975, including two new species and a rare one. Pseudovorticella zhejiangensis sp. n. differs from its congeners mainly by having a conical-shaped zooid, conspicuous pellicular blisters, one ventral and one dorsal contractile vacuoles, and an infundibular polykinety 3 with three rows of nearly equal length but different beginning positions. Pseudovorticella dalianensis sp. n. can be defined mainly by an obovoid-shaped zooid, one ventral contractile vacuole, and a three-rowed infundibular polykinety 3 with the middle row being the longest. The rare species, Pseudovorticella verrucosa (Dons, 1915) Sun et al., 2009, was redescribed. The small subunit (SSU) rDNA sequences of these three species were sequenced for the first time, the phylogeny of Pseudovorticella species was analyzed, and the results verified the non-monophyly of this genus. This study demonstrates that the morphologic and gene barcoding data are the optimum combination to disclose the biodiversity of ciliates.

Prolonged electrolysis injures the neural development of zebrafish (Danio rerio) - Chaoqun Zheng; Yan Gao; Jinling Zhu; Lin Gan; Mengmeng Wang; Wen Zhang; Shunqing Yang; Liuyan Yang (Environmental Science and Pollution Research, 2022)

Optimized thyroid transcription factor-1 core promoter-driven microRNA-7 expression effectively inhibits the growth of human non-small-cell lung cancer cells - Shipeng Chen; Lian Guan; Xu Zhao; Jing Yang; Longqing Chen; Mengmeng Guo; Juanjuan Zhao; Chao Chen; Ya Zhou; Yong Han; Lin Xu (Journal of Zhejiang University-SCIENCE B, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Temperature has a strong impact on the abundance and community structure of comammox Nitrospira in an Ultisol - Mengmeng Feng; Zi-Yang He; Jianbo Fan; An-Hui Ge; Shengsheng Jin; Yongxin Lin; Ji-Zheng He (Journal of Soils and Sediments, 2022)

Process Performance and Microbial Communities in Anaerobic Co-digestion of Sewage Sludge and Food Waste with a Lower Range of Carbon/Nitrogen Ratio - Yi Zheng; Pan Wang; Xinyu Yang; Peiru Lin; Yongjing Wang; Mengmeng Cheng; Lianhai Ren (BioEnergy Research, 2022)

Medicinal herbs and phytochemicals to combat pathogens in aquaculture - Mengmeng Li; Dongdong Wei; Shuaishuai Huang; Lin Huang; Fengqiao Xu; Qing Yu; Mingzhu Liu; Pengfei Li (Aquaculture International, 2022)

Mapping coastal wetlands in the Yellow River Delta, China during 2008–2019: impacts of valid observations, harmonic regression, and critical months - Zhanpeng Wang; Yinghai Ke; Mengmeng Chen; Demin Zhou; Lin Zhu; Junhong Bai (International Journal of Remote Sensing, 2021)

LINC00324 affects non-small cell lung cancer cell proliferation and invasion through regulation of the miR-139-5p/IGF1R axis - Meiqing Zhang; Baoquan Lin; Yaming Liu; Tengfei Huang; Mengmeng Chen; Duohuang Lian; Shilong Deng; Congwen Zhuang (Molecular and Cellular Biochemistry, 2020)

HDAC9 Polymorphisms Predict Susceptibility, Severity, and Short-Term Outcome of Large Artery Atherosclerotic Stroke in Chinese Population - Mengmeng Wang; Mengmeng Gu; Zibao Li; Bo Sun; Xi Cheng; Zhengze Dai; Shun Li; Lulu Xiao; Min Zhao; Zhaojun Wang; Ying Lin; Yahong Liu; et al. (Journal of Molecular Neuroscience, 2019)

Evaluating the lingering effect of livestock grazing on functional potentials of microbial communities in Tibetan grassland soils - Mengmeng Wang; Shiping Wang; Linwei Wu; Depeng Xu; Qiaoyan Lin; Yigang Hu; Xiangzhen Li; Jizhong Zhou; Yunfeng Yang (Plant and Soil, 2016)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Efficient photocatalytic degradation of tetracycline hydrochloride by Ag3PO4 under visible-light irradiation - QiShe Yan; MengMeng Xu; CuiPing Lin; JiFei Hu; YongGang Liu; RuiQin Zhang (Environmental Science and Pollution Research, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

Piperine potentiates the antidepressant-like effect of trans-resveratrol: involvement of monoaminergic system - Wu Huang; Zhuoyou Chen; Qiandong Wang; Mengmeng Lin; Shujuan Wu; Qizhi Yan; Fan Wu; Xuefeng Yu; Xupei Xie; Gaowen Li; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Noise-induced spatiotemporal patterns in Hodgkin–Huxley neuronal network - Ying Wu; Jiajia Li; Shaobao Liu; Jiazhi Pang; Mengmeng Du; Pan Lin (Cognitive Neurodynamics, 2013)